MULTINOMIAL LOGISTIC REGRESSION TO DETERMINE FACTORS INFLUENCING THE SELECTION OF HEALTH CARE FACILITIES IN INDONESIA - Sobari, Muhamad; Putri, Dian Islamiaty; Prama, Delvi Rutania; Suparman, Yusep (Journal of Fundamental Mathematics and Applications (JFMA), 2024)
Health facilities play a critical role in meeting the community's health needs. The existence of changes in lifestyle resulted in the community suffering from an increasing number of diseases, which increased the community's need for health facilities. There are two kinds of health facilities in Indonesia: government-owned health facilities and private health facilities. Both health facilities have advantages and disadvantages in terms of community service. As a result, Indonesians must make decisions about which health facilities to use in order to address health issues. The purpose of this research is to identify the factors that influence the selection of health facilities in Indonesia. Data from the Indonesia Family Life Survey (IFLS) 2015 were used in this study. This study uses four types of health facilities so the multinomial logistic regression method is appropriate. The findings of this study are all factors used in this study have a significant effect on the selection of health facilities. Jamkesmas ownership factors, gender, age, ability to move, and morbidity are significant on the three categories of response variables, namely public, private, and other health facilities. Askes ownership factor is significant in two categories, namely public and private health facilities. The marital status factor in the married category was significant in three categories, while divorced/widowed category was significant in two categories. While the five categories of education level factors were significant in other health facilities category.